Acetylcholinesterase inhibitors in treatment-resistant psychotic depression. Issue 1 (January 2018) - Smart, Chris; McAllister-Williams, Hamish; Cousins, David Andrew
Dopamine receptor antagonists can be effective in psychotic depression but response is not assured. Visual hallucinations may arise from a dysregulation of brain cholinergic systems and acetylcholinesterase inhibitors (AChEIs) can treat such hallucinations in dementia with Lewy bodies (DLB). AChEIs have been used in schizophrenia with some success but their efficacy and tolerability in psychotic depression is unclear. This striking case illustrates AChEIs specifically targeting multimodal hallucinations in treatment-resistant depression. To our knowledge it is the first case report to do so. It highlights the value of delineating psychopathology when considering novel interventions. This case also shows the idiosyncratic nature of side effects and the importance of pursuing different drugs within class.